2013
DOI: 10.1111/gcbb.12056
|View full text |Cite
|
Sign up to set email alerts
|

Carbon payback period and carbon offset parity point of wood pellet production in the South‐easternUnited States

Abstract: This study examines the effect of methodological choices to determine the carbon payback time and the offset parity point for wood pellet production from softwood plantations in the South-eastern United States. Using the carbon accounting model GORCAM we model low-, medium-and high-intensity plantation management scenarios for a single stand level, an increasing stand level and a landscape level. Other variables are the fossil-fuel reference system and the electrical conversion efficiency. Due to the large amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 32 publications
1
108
0
Order By: Relevance
“…We do not quantify the impact of the temporal delays in CO 2 emissions from decaying forest residues left on a forest site versus the CO 2 emissions that occur immediately if residues are instead supplied to a co-generation facility for fuel substitution. As a result, our cost assessment does not consider the temporal profiles of GHG emissions or periods of carbon debt repayment (such as presented in [39] and [25]), which can be quite short in the case of forest residues substituting for fossil fuels [20,21]. While a gradual decay of forest residues over several years does translate into delayed CO 2 emissions, our focus here is the development of indicative national cost curves.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We do not quantify the impact of the temporal delays in CO 2 emissions from decaying forest residues left on a forest site versus the CO 2 emissions that occur immediately if residues are instead supplied to a co-generation facility for fuel substitution. As a result, our cost assessment does not consider the temporal profiles of GHG emissions or periods of carbon debt repayment (such as presented in [39] and [25]), which can be quite short in the case of forest residues substituting for fossil fuels [20,21]. While a gradual decay of forest residues over several years does translate into delayed CO 2 emissions, our focus here is the development of indicative national cost curves.…”
Section: Methodsmentioning
confidence: 99%
“…For example, additional utility can be extracted from the capacity of forest biomass to offset GHG emissions when used to replace fossil fuel combustion for energy generation [20][21][22][23]. The combustion of residues can potentially achieve GHG emissions neutrality in a very short period [24,25]. A number of studies have demonstrated the use of various types of residual biomass for heat and electricity production [14,[26][27][28] and have found that residue biomass is only economically viable without government support when the avoided GHG emissions are given a market value.…”
Section: Introductionmentioning
confidence: 99%
“…However, greenhouse gas (GHG) emissions are reduced for empty return trips in comparison to loaded trucks. Jonker et al have assumed (based on Hamelinck et al [24]) a 60% GHG emission reduction for a 100-km distance for 16-32 ton empty versus loaded trucks [58]. Another question is to what product chain the emissions from return trips by loaded trucks would be allocated.…”
Section: Shipment In Bulk By Road Is Not Organized In Russia So It Imentioning
confidence: 99%
“…One important quality aspect is that a part of the dry matter of wood pellets is lost during handling in export ports and shipment [58], which decreases the heating value. Jonker et al [58] have assumed total dry matter loss of wood pellets as 7% for the whole supply chain from forest to power plant. The extent of the loss, however, depends on the specific supply chain.…”
Section: 2cargo Handling Options In the Seaportmentioning
confidence: 99%
See 1 more Smart Citation